Correlating hidden local structural distortion with antiferroelectric-ferroelectric transition in PbZrO3-based perovskites. (15th January 2023) - Liu, Hui; Sun, Zheng; Li, Ling; Gao, Baotao; Zhang, Yueyun; Qi, He; Kato, Kenichi; Roleder, Krystian; Ren, Yang; Chen, Jun
Abstract: Externally stimulated antiferroelectric-ferroelectric (AFE-FE) transition makes AFE materials attractive for many applications ranging from energy storage to sensing. This transition-mediated macroscopic electrical characteristics have been extensively investigated, yet the underlying structural evolution remains poorly understood. Herein, we study the local- and long-range structural evolutions in the Nb-doped Pb(Zr, Sn, Ti)O3 perovskites by in-situ X-ray total scattering and diffraction, which show three different types of AFE-FE transitions. The evolution of long-range structure from diffraction and local structure identified by atomic pair distribution function (PDF) are consistent well with the phase transition behavior indicated by macroscopic polarization/strain measurements, while discrepancies exist. Interestingly, frequently employed long-range structure picture that the uniform AFE pseudo-tetragonal to FE rhombohedral transformation is insufficient to understand the distinct composition-dependent AFE-FE transition behaviours. Instead, the reversibility of this transition correlates with the chemically sensitive local atomic displacements revealed by newly developed in-situ PDF. The critical electric field of transition is associated with the local structural differences between the AFE and FE state. The macroscopic electrostrains can be well estimated by the phase transition associated lattice strain and domain alignment from in-situ synchrotron XRD data, while the local strains calculated from in-situ PDFs are found to be much lower. These results provide a fresh insight into the AFE-FE transition, and advance the understanding of structure-property relationships in AFE materials. Graphical abstract: Image, graphical abstract